If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(-1y) = 7 Remove parenthesis around (-1y) 3x + -1 * -1y = 7 Multiply -1 * -1 3x + 1y = 7 Solving 3x + 1y = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + 1y + -1y = 7 + -1y Combine like terms: 1y + -1y = 0 3x + 0 = 7 + -1y 3x = 7 + -1y Divide each side by '3'. x = 2.333333333 + -0.3333333333y Simplifying x = 2.333333333 + -0.3333333333y
| 16x^7/-4x^3 | | 16x=36-3x | | x^2-16/x^2-3x-4= | | 2=r/3-1 | | 15×1/3 | | 20+x=36-3x | | 5x+3y=316 | | 9x-3(-5x-2)=8x | | 1/8x=50 | | 12x+28=18x-20 | | (8x-8)1.5=64 | | -1=4(3-x*2) | | x+x*x+x*x*x= | | 2x-3(-3)-2=4 | | (4x-16)0.5=36 | | 2(x+1)=-3(3x-2) | | 6.666+x=12-x | | 6(10-7n)=-42-8n | | 2*(-9)*3=(-54) | | -46=-14-4x | | -12v=-13.4v-18.48 | | 15*0.3= | | 2(.25)+1/2(x-2)=0.4x | | -12=-13.4v-18.48 | | 9=3(7x+2) | | (x+y)(30x+32768x-x)= | | -13-2y=7-11y+11y | | .50X+50=100 | | 18+h=-6h-17 | | 6m=5m-17 | | H(x)=1/0.5 | | 5*n*m+n=2m |